Kalam Khabari Dalam Syi’r Uhibbuki Jiddan Karya Nizar Qabbani: Kajian Ilmu Ma’ani - Sayid Muhamad Al Maliki; Rohanda Rohanda; Muhammad Abdul Halim (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
This study examines the use of Kalam Khabari in the poem “Uhibbuki Jiddan” by Nizar Qabbani through the framework of Ilm al Ma‘ani in Arabic rhetoric. The study aims to identify the types of Kalam Khabari, the forms of emphasis employed, and the rhetorical purposes that emerge in the text, as well as to explain their role in constructing the romantic tone of the poem. This research applies a qualitative descriptive method using a distributional approach. The data consist of poetic lines containing declarative structures, collected through careful and repeated reading, then identified, classified, and analyzed based on their structural forms and rhetorical functions. The findings reveal three main types of Kalam Khabari, namely ibtida’i, thalabi, and inkari, supported by various emphasis devices such as particles, repetition, and oath expressions. These structures function not only to convey information but also to express weakness, evoke awareness, convey emotional intensity, and invite compassion. The study shows that Kalam Khabari plays a significant role in strengthening meaning, intensifying emotional expression, and shaping the romantic character of the poem